ANALISIS DRUG RELATED PROBLEMS (DRPS) PADA PASIEN PENYAKIT GAGAL GINJAL KRONIK DI INSTALASI RAWAT INAP RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Mutiara Siahaan; Yuliana Tobing (Jurnal Kesehatan Sejahtera, 2024)
Chronic kidney disease (CKD) has become a growing global public health priority associated with high morbidity, mortality, and healthcare costs. Patients with chronic disease often require a combination of several drugs. The administration of these drug combinations is generally expected to have a beneficial effect, but in some cases drug interactions are found that result in ineffective treatment and the emergence of unexpected events and cause quite adverse effects both on clinical and on treatment costs. This study aims to determine the incidence of Drug Relate Problems (DRPs) in CKD patients at the Inpatient Installation of Imelda Workers General Hospital Medan. This study was a non-experimental study with descriptive observation that data collection was done retrospectively and analysed with descriptive methods. The sampling technique used the Slovin formula with a total of 60 patients during the January - March 2024 period. Analysis of drug interaction data based on Drug Interaction Checker and Drug Interaction Fact and classification of Drug Relate Problems (DRPs) according to Cipolle et.2012. The results showed that there were 3 occurrences of DRPs in CKD patients, namely: Too Low Drug Dosage 30 patients (68.18%), Unnecessary Drug Therapy there were 10 patients (22.73%) and Patient Non-Compliance there were 4 patients (9.09%). Interaction Based on Severity Major 27 cases, Moderate 202 cases, Minor 46 cases. Interaction based on mechanism of action Pharmaceutics 1 case, Pharmacokinetics 9 cases, and Pharmacodynamics 23 cases